2013
DOI: 10.1089/ham.2012.1054
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Exposure to Cytokines and Hypoxia Enhances Excitability of Oxygen-Sensitive Type I Cells in Rat Carotid Body: Correlation with the Expression of HIF-1α Protein and Adrenomedullin

Abstract: Liu, X., L. He, B. Dinger, L. Stensaas, and S. Fidone. Sustained exposure to cytokines and hypoxia enhances excitability of oxygen-sensitive type I cells in rat carotid body: Correlation with the expression of HIF-1a protein and adrenomedullin. High Alt Med Biol 14:53-60, 2013.-Recent studies in our laboratory demonstrated that chronic hypoxia (CH) induces a localized inflammatory response in rat carotid body that is characterized by macrophage invasion and increased expression of inflammatory cytokines. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…SH also induces several adaptive changes in peripheral chemoreflex pathways, such as, enhancement of gene transcription and excitability of glomus cells in carotid body (Wang et al, 2000;Ortiz et al, 2009;Liu et al, 2013). Long-term SH for 10 d also affected NTS neurons, which presented an increased NTS neuronal discharge due to an evoked excitatory inputs to NTS neurons, as well as a decrease in K ATP channel subunits expression (Kir 6.1 and Kir 6.2 subunits; Zhang et al, 2008Zhang et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…SH also induces several adaptive changes in peripheral chemoreflex pathways, such as, enhancement of gene transcription and excitability of glomus cells in carotid body (Wang et al, 2000;Ortiz et al, 2009;Liu et al, 2013). Long-term SH for 10 d also affected NTS neurons, which presented an increased NTS neuronal discharge due to an evoked excitatory inputs to NTS neurons, as well as a decrease in K ATP channel subunits expression (Kir 6.1 and Kir 6.2 subunits; Zhang et al, 2008Zhang et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Extended hypoxia increases inflammatory cytokine expression in the rat carotid body and augments the sensory response to hypoxia (Liu et al . ). Our previous study showed that human carotid bodies express genes encoding pro‐inflammatory cytokines (Mkrtchian et al .…”
Section: Resultsmentioning
confidence: 97%
“…; Liu et al . ). In line with this, we observed a suppressed or blocked release of cytokines by hypoxia from one patient in the present study who received parecoxib prior to the removal of the carotid body.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations